2017
DOI: 10.1213/ane.0000000000001899
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Link Between Postextubation Pneumonia and Ventilator-Associated Pneumonia: An Experimental Study

Abstract: Introduction The presence of an endotracheal tube is the main cause for developing ventilator associated pneumonia (VAP), but pneumonia can still develop in hospitalized patients after endotracheal tube removal (Post-Extubation Pneumonia, PEP). We hypothesized that short-term intubation (24h) can play a role in the pathogenesis of PEP. To test such hypothesis, we initially evaluated the occurrence of lung colonization and VAP in sheep that were intubated, and mechanically ventilated for 24h. Subsequently, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Colonized subglottic secretions that leak across the folds of the ETT cuff, 7 ineffective mucociliary clearance caused by the cuff, 5 impairment of the protective cough reflex after endotracheal intubation, 19 aerosolization of the biofilm along the inner surface of the ETT that acts as a bacterial reservoir, 20 and the development of atelectasis 21 all contribute to increase the risk of lung colonization and, eventually, pneumonia. Furthermore, in the semirecumbent position, gravity directly acts on lung colonization and pneumonia, as described in both animal models 4,7,8,22 and human subjects, 23,24 and as recently confirmed by the Gravity-trial Network. 24 As shown in clinical studies, although the shape does not affect the frequency of pneumonia, 25,26 the material of the ETT cuff can exhibit a different performance in terms of pneumonia prevention.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Colonized subglottic secretions that leak across the folds of the ETT cuff, 7 ineffective mucociliary clearance caused by the cuff, 5 impairment of the protective cough reflex after endotracheal intubation, 19 aerosolization of the biofilm along the inner surface of the ETT that acts as a bacterial reservoir, 20 and the development of atelectasis 21 all contribute to increase the risk of lung colonization and, eventually, pneumonia. Furthermore, in the semirecumbent position, gravity directly acts on lung colonization and pneumonia, as described in both animal models 4,7,8,22 and human subjects, 23,24 and as recently confirmed by the Gravity-trial Network. 24 As shown in clinical studies, although the shape does not affect the frequency of pneumonia, 25,26 the material of the ETT cuff can exhibit a different performance in terms of pneumonia prevention.…”
Section: Discussionsupporting
confidence: 54%
“…This caused inflammation of the lung parenchyma and led to hypoxemia, a pathophysiologic sign of respiratory failure. 4,5,7,8 Results of our study indicated that the change of a single variable during intubation and mechanical ventilation (ETT cuff) might play a major contributing role in the multifaceted pathogenesis of VAP because it can radically influence the risk of lung bacterial colonization.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Endotracheal intubation and mechanical ventilation considerably impair airway defenses, increasing the risk of bacterial colonization and ventilator-associated pneumonia. 2,3 The endotracheal tube (ETT) cuff, which allows positivepressure ventilation and prevents aspiration, compromises mucociliary clearance by mechanically preventing the flow of mucus toward the oropharynx. 4,5 Therefore, secretions accumulated in the trachea must be removed by endotracheal suctioning.…”
Section: Introductionmentioning
confidence: 99%